Solubility, Permeability, and Dissolution Rate of Naftidrofuryl Oxalate Based on BCS Criteria - Marta Kus-Slowinska; Monika Wrzaskowska; Izabela Ibragimow; Piotr Igor Czaklosz; Anna Olejnik; Hanna Piotrowska-Kempisty (MDPI AG, 2020)
The Biopharmaceutics Classification System (BCS) was conceived to classify drug substances by their in vitro aqueous solubility and permeability properties. The essential activity of naftidrofuryl oxalate (NF) has been described as the inhibition of the serotonin receptors (5-HT2), resulting in vasodilation and decreasing blood pressure. Since the early 1980s, NF has been used to treat several venous and cerebral diseases. There is no data available on the BCS classification of NF. However, based on its physical-chemical properties, NF might be considered to belong to the 1st or the 3rd BCS class. The present study aimed to provide data concerning the solubility and permeability of NF through Caco-2 monolayers and propose its preliminary classification into BCS. We showed that NF is a highly soluble and permeable drug substance; thus, it might be suggested to belong to BCS class I. Additionally, a high dissolution rate of the encapsulated NF based on Praxilene® 100 mg formulation was revealed. Hence, it might be considered as an immediate-release (IR).